Comparison of optical-feedback cavity-enhanced absorption spectroscopy and gas chromatography for ground-based and airborne measurements of atmospheric CO concentration - Ventrillard, Irène; Schmidt, Martina (Atmospheric measurement techniques, 2017)
We present the first comparison of carbon monoxide (CO) measurements performed with a portable laser spectrometer that exploits the optical-feedback cavity-enhanced absorption spectroscopy (OF-CEAS) technique, against a high-performance automated gas chromatograph (GC) with a mercuric oxide reduction gas detector (RGD). First, measurements of atmospheric CO mole fraction were continuously collected in a Paris (France) suburb over 1 week. Both instruments showed an excellent agreement within typically 2ppb (part per billion in volume), fulfilling the World Meteorological Organization (WMO) recommendation for CO inter-laboratory comparison. The compact size and robustness of the OF-CEAS instrument allowed its operation aboard a small aircraft employed for routine tropospheric air analysis over the French Orléans forest area. Direct OF-CEAS real-time CO measurements in tropospheric air were then compared with later analysis of flask samples by the gas chromatograph. Again, a very good agreement was observed. This work establishes that the OF-CEAS laser spectrometer can run unattended at a very high level of sensitivity ( < 1ppb) and stability without any periodic calibration.
Gesehen am 24.09.2018